Naturally occurring gold nanoparticles and nanoplates - Hough, R.; Noble, R.; Hitchen, G.; Hart, Robert; Reddy, Steven; Saunders, M.; Clode, P.; Vaughan, D.; Lowe, J.; Gray, D.; Anand, R.; Butt, C.; et al. (Geological Society of America Inc, 2008)
During the weathering of gold deposits, exceptionally pure, <200 nm diameter, nanoparticulate gold plates (6 nm thick) are formed. The particles display controlled growth of both size and shape and signs of assembly to form belts and sheets. The gold is associated and intergrown with minerals formed by evaporation and is interpreted to have been deposited rapidly from saline groundwater during a drying event. The size and morphology of the gold nanoparticles and nanoplates are identical to the products of experimentally manufactured gold colloids. This represents the fi rst direct observation of colloidal nanoparticulate gold in nature, confi rming this as an active mechanism of gold transport during the weathering of gold deposits.